Entre os atos de Kira e o fascismo na animação death note: representação de um mundo distópico - Passos, Marcelo Martins (2024)
The research aims to analyze the concepts of dystopia and fascism through the actions of the character Kira in the animated series Death Note, an adaptation of the eponymous manga by Tsugumi Ohba, produced by the MadHouse studio under the direction of Tetsurō Araki between 2006 and 2007. This series combines the genres of drama, suspense, mystery, and crime. Death Note tells the story of a young man who, after discovering a notebook capable of killing anyone whose name is written in it, decides to use this tool to eliminate criminals and create what he believes to be a better world. From this premise, the characters are plunged into a profound social chaos. By analyzing these actions in light of the concepts of fascism and dystopia, the research conducts a filmic analysis of selected scenes using cinematic theories such as camera angles, framing, Edgar Morin’s projection-identification theory (1970), the approach to cinema and violence by Luís Nogueira (2002), cinematographic techniques, and the use of color. These elements are further examined alongside philosophical and sociological concepts of fascist ideology as outlined by Robert O. Paxton (2007) and Hannah Arendt (1979; 1985; 1999), and their relationship to the concept of dystopia as discussed by Gregory Claeys (2017), Karl Mannheim (1976), and Emil Cioran (2011). These theoretical frameworks engage in dialogue with the technical and narrative aspects highlighted in the selected scenes.The normalization of violence, authoritarianism, the politics of death, and religiosity are also addressed. This leads to a key inquiry: How are authoritarianism, the politics of death, religiosity, and other themes depicted in the animation? Does Kira's instrumentalization of the Death Note as a tool of justice point to a dystopian future? To what extent does the animated medium contribute to audience identification and reflection on these themes?The investigation encompasses the 37 episodes that comprise the research corpus and concludes that there exists a tangible possibility of a dystopian future, as Kira subjugates Japan’s entire population through his authoritarian rule and politics of extermination. The animated medium appears to enable the dissemination of such themes, as discussed throughout the research, to a broader audience, fostering critical reflection and deeper studies on fascism and dystopia.